A Review of the Impact of EFL Teachers’ Affectivity and Surgency and Learners’ Shyness on Their Language Attainment - Tian, Tian (Frontiers in Psychology, 2022)
Teaching is considered as a complex and demanding profession affected by a number of student-related and teacher-related factors. Instructors’ personality trait has been long scrutinized as an influential issue, which can facilitate or impede the learning process. Teachers’ affective factors and personality types (e.g., surgency) are among the most commonly studied aspects of educational research, particularly English as a Foreign Language (EFL) teachers. The review of related studies suggests that extrovert teachers are more likely to encourage EFL learners to pursue their educational objectives and master the target language effectively because they can create friendly and positive learning conditions where learners are engaged in classroom activities. This will be primarily prominent for EFL learners with higher levels of shyness. Such students prefer to remain reticent during the course, evade engaging in collaborative tasks, and tend to use a number of avoidance strategies while facing a stressful situation. Hence, language teachers are recommended to employ a variety of techniques as well as appropriate tasks in order to help these pupils overcome their negative affective characteristics so that they can enjoy learning the content and producing the target language in a facilitating and inspirational atmosphere.